The Use of Polyvinyl Alcohol’s Complexes for Plants Protection Against Diseases and Pests - Prosanov, Igor (New Environmentally-Friendly Materials, 2025)
The research is devoted to elaboration of new materials for agricultural use what is regarded as an urgent need for environment pollution decrease and enhancing of farming efficiency. Gel of polyvinyl alcohol complexed with boric acid or borax is suggested first time as the base of “aroma fixative” for volatile compounds possessing by insect repelling effect. Some new principles are discussed in favor of replacement of common inorganic pesticides like copper compounds on their polymeric complexes. The main positions among them are: 1) formation of biocidal coverings relatively stable at different weather conditions; 2) better adherence of preparations to a surface of protected plant; 3) possibility of biocidal activity mitigation and 4) homogeneity of biocidal coverings. Mitigated biocidal activity is regarded in relation with preparations’ influence on plants. An impact on plants and safeguarding behavior against plant diseases and pests were investigated for polyvinyl alcohol’s complexes with boric acid and borax, copper hydroxychloride and hydroxide, iron(III) chloride and tar. Their efficiency against spider mite, Colorado beetle and tomato diseases was discovered. It is expected that their use will allow drastic decrease in pesticides’ side action, expenses and environmental pollution in agriculture. Thus, the need for the following deeper investigations of above mentioned materials in farming is substantiated.